HISTORY AND CONSUMPTION OF COFFEE IN BRAZIL AND IN THE WORLD - Nicikava, Antônio Carlos; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
Agribusiness has always been one of the most admirable sources of wealth in Brazil. The seriousness of Brazilian agribusiness has made the country one of the most competitive in the world in terms of production. This article aims to analyze the international agribusiness trade and its growth. To conduct research, seek information from the most recent literature in the field of international agribusiness trade, relevant to the scientific community: journal articles, dissertations, electronic media articles and academic books. It was later discovered that Brazil has been taking advantage of the opportunities offered by world trade in the last decade, from a fragile state in the late 1990s to a peak in the 2009-2011 triennium. The conclusion is that the importance of agribusiness for the Brazilian economy and the position it has conquered in the current world conjuncture is indisputable. The present work sought to understand the importance of coffee farming for the Brazilian economy, as well as the process of innovations in this agrifood chain and its impacts on the productivity of this grain. The new forecast for the world’s largest coffee producer and exporter was above Conab’s September projection of 61.6 million bags, also beating the previous record set in 2018.